Dust maker a volcanic ash dispersion unit - Eiður Örn Þórsson 1979- (2015)
Ash clouds from volcanic eruptions can be the source of airspace being closed for some time, greatly affecting airtraffic. To predict and analyze the hazard, these conditions need to be simulated in a controlled environment. The primary objective of this thesis it to develop, produce and test a small prototype that is capable of dispersing fine particle volcanic ash in a controlled manner, suitable for use in a volcanic ash plume simulator. The ash sample used for testing came from the 2010 eruption in Eyjafjallajökull. In order to extend the time that the ash particles are suspended in the air, the sample was sifted to a sub 75 µm particle size. The mean particle diameter within that sample is ≈ 35 µm. Experiments were conducted on the sample to determine it’s angle of repose of 69 ◦ and density of 1098 kg/m^3. A prototype device was built and several experiments were performed with different feed rates and times, resulting in repeatability in ash output of ± 10.1 % from the nominal value with a confidence level of 99.7 %. This gives reason to investigate the device further and ultimately create a large scale ash plume of concentrations of interest. That ability would further aid the research into “Ash detectors mechanisms” for modern aviation and reduce closed airspace in the event of a similar eruption as in the case of Eyjafjallajökull in 2010. Öskuský frá eldfjöllum geta og hafa lokað loftrýmum sem hafa töluverð áhrif á flugumferð. Til að spá fyrir og rannsaka þessi áhrif er nauðsynlegt að geta endurskapað slíkar aðstæður undir eftirliti. Meginmarkmið verkefnisins er að hanna, smíða og prufa smækkaða frumgerð af apparati sem með stýranlegum hætti er fært um að mata út fínni eldfjallaösku, heppilegri til að herma öskuský. Öskusýnið sem notast er við kemur úr gosinu í Eyjafjallajökli 2010. Til að lengja tímann sem agninrnar hanga í loftinu var sýnið sigtað í kornastærðir minni en 75 µm en meðalþvermál agna innan þess sýnis er u.þ.b ≈ 35 µm. Tilraunir voru framkvæmdar á sýninu til þess að ákvarða hvíldarhorn ...